Embracing Complexity beyond Systems Medicine: A New Approach to Chronic Immune Disorders - te Velde, Anje A.; Bezema, Tjitske; van Kampen, Antoine H. C.; Kraneveld, Aletta D.; 't Hart, Bert A.; van Middendorp, Henriët; Hack, Erik C.; van Montfrans, Joris M.; Belzer, Clara; Jans-Beken, Lilian; Pieters, Raymond H.; Knipping, Karen; et al. (Frontiers in Immunology, 2016)
In order to combat chronic immune disorders (CIDs) it is an absolute necessity to understand the bigger picture, one that goes beyond insights at a one-disease, molecular, cellular and static level. To unravel this bigger picture we advocate an integral, cross-disciplinary approach capable of embracing the complexity of the field. This paper discusses the current knowledge on common pathways in CIDs including general psychosocial and lifestyle factors associated with immune functioning. We demonstrate the lack of more in-depth psychosocial and lifestyle factors in current research cohorts and most importantly the need for an all encompassing analysis of these factors. The second part of the paper discusses the challenges of understanding immune system dynamics and effectively integrating all key perspectives on immune functioning, including the patient perspective itself. The paper suggests the use of techniques from complex systems science in describing and simulating healthy or deviating behaviour of the immune system in its biopsychosocial surroundings. The patient perspective data are suggested to be generated by using specific narrative techniques. We conclude that to gain more insight into the behaviour of the whole system and to acquire new ways of combatting CIDs, we need to construct and apply new techniques in the field of computational and complexity science, to an even wider variety of dynamic data than used in today’s systems medicine.